Big data Interoperability framework for Malaysian public open data - Muhamad Ibrahim, Najhan; Amir Hussin, Amir 'Aatieff; Hassan, Mohd Khairul Azmi; Breathnach, Ciara (Springer, 2021)
Massive quantities of Malaysia Open Data are available in the public domain such as provided by data.gov.my. However, most of the available datasets are not integrated. Some are unstructured and structured following its source of datasets. Naturally, the datasets cannot interconnect or ‘interoperable’ with one another, which leads to Big Data (BD) problem. Advances in the database management system and interconnect linked data techniques to connect database systems, provide extraordinary opportunities to create relationships between distributed datasets for a particular objective. Fast-growing in computing technologies, which lead to the digitization, which lead to the capability to query various open datasets. Public Open Data come in varying sources, sizes, and formats. These Big and Small datasets formats pose various integration problems for Information Technology Frameworks. To generate meaningful linked-data to support the purposes of our study the relationship between these disparate datasets needs to be identified and integrated. This paper proposes a BD interoperability framework to integrate Malaysian public health open data. The main goal to enable the potential application with current technologies to extract and discover from Public Open Data. It would reduce the overall cost for healthcare with better prevention mechanism to be placed at the right time. By having a public open big data framework in health, we would predict the pattern of future disease that may take several years to understand.